An investigation into syntactic and semantic features of thinking verbs in english and vietnamese - Huỳnh,Thị Tuyết Nhung (ĐHNN, 2016)
Based on the theories of semantics and syntax of words and phrases, this study on ―An Investigation on Semantic and Syntactic Features of Thinking Verbs in English and Vietnamese” in attempt to find out the similarities and differences in semantics and syntax to suggest some implications for teaching English to Vietnamese learners, especially journalism students. These two sets of data are structurally described and contrastively analyzed under quantitative and quatative approachs. The source consists of Thinking Verbs from some stories in English and in Vietnamese. The findings of the study show that Thinking Verbs from stories in English and Vietnamese are different in structure patterns, in the frequency or in the formality of words and phrases, but have some similarities in the meaning nuances. Hopefully, the result of the study can be somewhat beneficial for the teaching and learning of English. This study is also helpful for journalism students as well as reporters in writing texts.
Keywords: syntactic and semantic